Methodological considerations for determining the volume and intensity of drop jump training. A systematic, critical and prepositive review - Montoro-Bombú, Raynier; Sarmento, Hugo; Buzzichelli, Carlo; Moura, Nelio Alfano; Gonzáles Badillo, Juan José; Santos, Amândio; Rama, Luís (Frontiers in Physiology, 2023)
This systematic review provides critical and propositional information on criteria for determining the volume and intensity of drop jumps during plyometric training programs. Eligibility criteria were defined according to PICOS: Participants: male or female athletes, trained or recreationally active (16–40 years). Intervention duration: more than four weeks. Comparators: passive or active control group during a plyometric training program. Results: Drop Jump or Depth Jump with other jumps, acceleration, sprint, strength, and power output. Outcomes: information on improvement. Design: randomized controlled trials. We searched articles published in PubMed, SPORTDiscus, Web of Science, and Scopus. The search was conducted until 10 September 2022 for English-language articles only. The risk of bias was assessed using Grading of Recommendations, Assessment, Development and Evaluation (GRADE) for randomized controlled studies. We identified 31495 studies, of which only 22 were included. We found that six groups presented results with women, 15 presented results with men, and the remaining four presented mixed studies. Of the 686 people recruited, 329 participants aged 25.79 ± 4.76 years were involved in training. Methodological problems in training intensity, volume distribution, and individualization were noted, but methodological recommendations for their solution are also provided. It is concluded that the drop height should not be understood as the intensity determinant of plyometric training. Intensity is determined by ground reaction forces, power output, and jump height, among other factors. Furthermore, the athletes' experience level selection should be based on the formulas recommended within this research. These results could be helpful for those who intend to conduct new plyometric training programs and research.